2018
DOI: 10.1111/1756-185x.13337
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 rs3761548 polymorphism is associated with knee osteoarthritis in a Turkish population

Abstract: Our findings indicated that the association between FOXP3 rs2232365 polymorphism and knee OA tended to yield negative results but the FOXP3 rs3761548 C allele was associated with elevated risk of OA in Grade 4 knee OA patients in a Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…We thought that the conflicting observations were conduced mainly by ethnic and geographic differences. Mutation of the genotype of rs3761548 mostly affects the expression and activity of FOXP3 protein, which was further involved in many autoimmune diseases including rheumatoid arthritis [42], allergic rhinitis [43], and autoimmune thyroid disease [44]. Our study showed that FOXO3 rs3761548 was not found to be related to preeclampsia in Northeast women of China based on the present date.…”
Section: Summary Of Key Resultsmentioning
confidence: 53%
“…We thought that the conflicting observations were conduced mainly by ethnic and geographic differences. Mutation of the genotype of rs3761548 mostly affects the expression and activity of FOXP3 protein, which was further involved in many autoimmune diseases including rheumatoid arthritis [42], allergic rhinitis [43], and autoimmune thyroid disease [44]. Our study showed that FOXO3 rs3761548 was not found to be related to preeclampsia in Northeast women of China based on the present date.…”
Section: Summary Of Key Resultsmentioning
confidence: 53%
“…This minor allele frequency (MAF) is in line with the Egyptian study (0.34), [43] but different from those reported in Turkish and Indian populations, 0.61 and 0.56, respectively. [44,45] This variability in the results of the studies may be due to ethnic factors and the size of the sample studied [Table 3].…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Regarding the -924 G > A (rs2232365), we did not find any association of this variant and SLE susceptibility and clinical parameters. Although the -924 G > A FOXP3 variant (rs2232365) was evaluated in other autoimmunity diseases [23][24][25] this is the first study to evaluate this variant in SLE patients. The G > A substitution of FOXP3 -924 is located in a putative-binding site for the transcription factor GATA-3 39 .…”
Section: Discussionmentioning
confidence: 99%